Aspects of knowing : epistemological essays - Hetherington, Stephen Cade (Perspectives on cognitive science (Amsterdam, Netherlands), 2006)
The overall aim of the series is to capture the interdisciplinary nature of the broad field of cognitive science with a range of volumes including anthologies which are either thematically related or more diverse in their contents. Proposals are welcome for volumes concerning any topics across the wide range of cognitive science fields. Possible themes to be explored include Music and Cognition, Decision Making and Behavioral Finance, Education and Cognition, Cognitive Science of Science, Historical Foundations of Cognitive Science, Imagery, Evolutionary Psychology, Consciousness, and Language.